Discovering the participation rights of children in Sweden and Vietnam: a study about Vietnamese parents' perspectives towards influencing factors on children's participation rights practices in the families - Chau, Nguyen Thi Minh (2018)
Children’s participation rights have been considered as one of the most radical and democratic rights of children that not only aim at protecting children’s rights but also enhance children’s competence and thus, giving children a higher position in the society. The aim of the study is to explore social and cultural factors that influence the practice of children’s participation rights in Vietnamese families in Vietnam and Sweden so as to contribute to a better understanding of the meaning of children’s participation rights in different contexts. Hence, qualitative method and semi-structure interviews have been employed for gathering parents’ experiences and opinions in relation to children’s participation rights. Ecological Theory has been employed in order to study children’s participation rights from macro level to micro level. Especially, The Family Change Theory and Family Change Model has been applied to explore the interrelationship between parents and children in the family so as to understand how parenting orientations influence the participation rights of children. The findings show that factors influencing children’s participation are embedded in a broad system from macro level to micro level. From macro level, cultural values are one of the constraining factors to the implementation of children’s participations rights. Besides, parents’ perspectives towards children’s competence are one of the factors creating the barriers to children’s participation rights practice. On the other hand, welfare policies for children and families in Sweden are considered as enabling conditions to support children’s participation rights practices whereas the lack of welfare policies for Vietnamese families in Vietnam may become a constraining condition. More importantly, it appears from the data that Vietnamese parents in both Vietnam and Sweden showed positive views toward children’s participation in decision-making process. Children’s voices have been listened and taken into consideration with due weight. Nevertheless, the age and experiences of the child contribute to the variations in practicing participation rights considerably. Furthermore, the Family Change Model provided insights on how the interrelationship between parents and children affect children’s participation and children’s autonomy. The study finds that the Interdependent Family Model is more common among Vietnamese parents in Vietnam with the childrearing orientation towards obedience and family loyalties. On the other hand, Vietnamese families in Sweden have the patterns of the Emotional Interdependence Family Model with higher level of autonomy and focus more on emotional bonds. Lastly, the Vietnamese parents living in Sweden show a sense of ambivalence towards the roles of adult children for the elderly care in the future.